2013
DOI: 10.1371/journal.pone.0065342
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Evolution of Non-O1/Non-O139 Vibrio cholerae by Multilocus Sequence Typing

Abstract: Pathogenic non-O1/non-O139 Vibrio cholerae strains can cause sporadic outbreaks of cholera worldwide. In this study, multilocus sequence typing (MLST) of seven housekeeping genes was applied to 55 non-O1/non-O139 isolates from clinical and environmental sources. Data from five published O1 isolates and 17 genomes were also included, giving a total of 77 isolates available for analysis. There were 66 sequence types (STs), with the majority being unique, and only three clonal complexes. The V. cholerae strains c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 68 publications
6
78
1
2
Order By: Relevance
“…These findings are consistent with a recent report by Octavia et al, in which 77 clinical and environmental non-O1/O139 isolates from a number of different countries were found to form 66 STs (13). The majority of these STs were unique, and only three clonal complexes were formed; as in our study, the clonal complexes cen- tered on epidemic or pandemic, ctx-positive strains, highlighting the close phylogenetic relationship among such strains, in contrast to the diversity seen among non-O1/O139 strains.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with a recent report by Octavia et al, in which 77 clinical and environmental non-O1/O139 isolates from a number of different countries were found to form 66 STs (13). The majority of these STs were unique, and only three clonal complexes were formed; as in our study, the clonal complexes cen- tered on epidemic or pandemic, ctx-positive strains, highlighting the close phylogenetic relationship among such strains, in contrast to the diversity seen among non-O1/O139 strains.…”
Section: Discussionsupporting
confidence: 92%
“…MLST was performed as described previously (13). Seven housekeeping genes were targeted for MLST analysis: adk, gyrB, metE, mdh, pntA, purM, and pyrC (see Table S2 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also regularly isolated from marine vertebrates, algae, sediment, or directly from the water column (7). Perhaps owing to the wide variety of such macro-and microhabitats, V. cholerae displays a large degree of genetic diversity (8)(9)(10)(11). Horizontal gene transfer by transduction (12), transformation (13), or conjugation (14) is a major factor in the creation of this diversity.…”
mentioning
confidence: 99%
“…Unfortunately, there are no genome sequence-based data for recombination in environmental strains, but several MLST studies on environmental strains have shown high diversity, indicating high recombination rates, which have also been supported by several additional criteria (44)(45)(46). Each of these referenced studies used strains with a sampling bias toward human-associated strains in countries with often inadequate treatment of sewage, adding the complication that some of the "environmental" strains were from fecal contamination.…”
Section: Significance Of the Asian Homeland-middle East-makassar Migrmentioning
confidence: 99%